Canada. Significant achievements 2015 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Canada during 2015 are identified, with respect to the needs and interests of the country, strengthening issues such as imports, animal health, beekeeping, exports, water use, loss control, satellite technologies and in resilience against climate change. Finally, the value chains of avocado, cocoa and the control of animal and plant diseases, such as Nosema ceranae, were supported.